ANALISIS PENGARUH ORIENTASI INOVASI, DUKUNGAN PROMOSI DAN DUKUNGAN TENAGA PENJUALAN TERHADAP KINERJA PRODUK DI PASAR - Asepta Hendriyanto (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
This study analyzes the effect of innovation orientation, promotionalsupport and sales force support on product performance in the market inorder to improve sustainable competitive advantage. The research problemthat is proposed fully refers to the research problems that is; there is atendency to increase the number of cabin numbers Prepaid sympathy, whichmeans the cessation of customers using Simpati Prepaid products based ondata from April 2004 to January 2005, and research gap from previousresearch, therefore, the formulation of this research problem is aboutimproving product performance in the market by basing on innovationorientation, promotional support and sales support to enhance sustainablecompetitive advantage. Furthermore, variable and indicator of research alsobased on previous research. A model has been developed and four hypotheseshave been formulated to address this research problem. Sampling techniqueis two technique (double sampling) that is, purposive samplingmethod andmethod of quota sampling. Respondents from this study amounted to 100respondents, where respondents are the owners or managers of retail andcellular prime amounting to 100.The data analysis used is Structural Equation Modeling (SEM) inAMOS 4.01 program. The results of this research data analysis show themodel and research results can be received well. And furthermore, the resultof this research proves that innovation orientation has positive andsignificant effect on product performance in the market, then it is formulatedthe support of sales force on product performance in market is positivelysignificant, empirical evidence shows promotional support is positive forproduct performance in market, further can be concluded that each constructhas gained justification and empirical evidence of sustainable competitiveadvantage through product performance in the market is positive andsignificantly influential.